Calibration of colour gradient bias in shear measurement using HST/CANDELS data. Issue 4 (16th March 2018) - Er, X; Hoekstra, H; Schrabback, T; Cardone, V F; Scaramella, R; Maoli, R; Vicinanza, M; Gillis, B; Rhodes, J
Abstract : Accurate shape measurements are essential to infer cosmological parameters from large area weak gravitational lensing studies. The compact diffraction-limited point spread function (PSF) in space-based observations is greatly beneficial, but its chromaticity for a broad-band observation can lead to new subtle effects that could hitherto be ignored: the PSF of a galaxy is no longer uniquely defined and spatial variations in the colours of galaxies result in biases in the inferred lensing signal. Taking Euclid as a reference, we show that this colour gradient bias (CG bias) can be quantified with high accuracy using available multicolour Hubble Space Telescope ( HST ) data. In particular we study how noise in the HST observations might impact such measurements and find this to be negligible. We determine the CG bias using HST observations in the F606W and F814W filters and observe a correlation with the colour, in line with expectations, whereas the dependence with redshift is weak. The biases for individual galaxies are generally well below 1 per cent, which may be reduced further using morphological information from the Euclid data. Our results demonstrate that CG bias should not be ignored, but it is possible to determine its amplitude with sufficient precision, so that it will not significantly bias the weak lensing measurements using Euclid data.